An evaluation of the effects of mindfulness training from the perspectives of wheelchair basketball players. (July 2018) - MacDonald, Luke A.; Oprescu, Florin; Kean, Bridie M.
Abstract: Objectives: Previous research has highlighted that mindfulness training (MT) is associated with an attenuation in physiological stress in wheelchair basketball players during competition. However, players' perceptions of how MT affected their sporting and everyday life were yet to be determined. Therefore, the present study evaluated the perceived impact of an 8-wk MT intervention on wheelchair basketball players by gathering and analysing the perspectives of the participants in the study. Design: Experimental qualitative design. Methods: Eight wheelchair basketball players completed an 8-wk MT intervention (meditations and mindfulness exercises; five times each week) during a competition period. Participants completed an evaluation survey which explored the impact of the MT intervention. Results: 8 wk of MT was beneficial in various aspects of the participants'' everyday lives, games and training in the form of improved concentration, improved sleep, better stress management, awareness, as well as improved foul shooting accuracy and regulation of heart rate. Conclusions: MT may be efficacious in improving both athletic performance and everyday life in para-athletes. Highlights: Qualitative reflections of para-athletes provide valuable insight into the efficacy of interventions. Wheelchair basketball players evaluated the impacts of a mindfulness training intervention. Perceived improvements in sporting and everyday life were reported. Mindfulness training may be beneficial in improving performance in para-sport.